Instrumen Hukum Tanggung Jawab Negara Terhadap Kesehatan Lingkungan Sebagai Hak Asasi Manusia - Theo Alif Wahyu Sabubu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the legal instruments regulating state responsibility toward environmental health as a fundamental human right and to evaluate the implementation of strict liability principles within the Indonesian legal framework. Main Problem: Despite the constitutional guarantee under Article 28H Paragraph (1) of the 1945 Constitution, a significant gap persists between legal ideals and the reality of environmental degradation, often exacerbated by economic exploitation and suboptimal state supervision. Method: This study employs a normative legal research method with a statutory approach and a conceptual approach, utilizing qualitative-prescriptive analysis on primary and secondary legal materials. Findings: The findings reveal that while Indonesia has established an integrated legal framework—comprising human rights law, environmental management law, and the latest healthcare regulations—state enforcement remains sub-optimal. This issue is particularly evident in regional autonomy, where a conflict of interest often arises between regional economic revenue and environmental protection. Furthermore, the application of strict liability has not been consistently integrated into administrative supervisory functions to prevent corporate pollution. Conclusion: To fully fulfill its constitutional obligation to protect and fulfill the right to a healthy environment, the state must shift from a reactive stance to a proactive approach by strengthening preventive instruments and strictly enforcing administrative sanctions.